Effects of financial literacy and attitude toward money on financial capability among SMEs in Malaysia - Mohamed, Mas Azira; Faizal, Sellywati Mohd; Jaffar, Nahariah (International Journal of Management and Sustainability, 2024)
The study examines how financial literacy and attitudes towards money affect financial capability among SMEs in Malaysia. SMEs are crucial for global economic growth but frequently encounter specific obstacles that include financial instability. This study investigates the factors that influence the financial capability of SME owners, acknowledging its importance in promoting business expansion and adaptability. The study involves 231 SME owners and uses scales to assess financial literacy, attitudes towards money, and financial capability. Results show significant correlations among financial literacy’s dimension and financial capability. Financial literacy is a crucial factor in determining financial capability, underscoring the need to improve financial education for SME owners. One dimension of attitude towards money, which is price sensitivity, shows a significant relationship with financial capability. According to the study, SME owners should devote time and effort to financial education and training in order to improve their financial capability. This can help SMEs in decision-making, hence improving the financial performance of the business. The study provides important information for policymakers, business owners, and researchers, highlighting the necessity of specific actions to enhance financial knowledge and encourage beneficial financial practices among SMEs.